UK endoscopy workload and workforce patterns: is there potential to increase capacity? A BSG analysis of the National Endoscopy Database. Issue 2 (20th June 2022) - Beaton, David; Sharp, Linda; Trudgill, Nigel John; Thoufeeq, Mo; Nicholson, Brian D; Rogers, Peter; Docherty, James; Penman, Ian D; Rutter, Matt
Abstract : Background: The lack of comprehensive national data on endoscopy activity and workforce hampers strategic planning. The National Endoscopy Database (NED) provides a unique opportunity to address this in the UK. We evaluated NED to inform service planning, exploring opportunities to expand capacity to meet service demands. Design: Data on all procedures between 1 March 2019 and 29 February 2020 were extracted from NED. Endoscopy activity and endoscopist workforce were analysed. Results: 1 639 640 procedures were analysed (oesophagogastroduodenoscopy (OGD) 693 663, colonoscopy 586 464, flexible sigmoidoscopy 335 439 and endoscopic retrograde cholangiopancreatography 23 074) from 407 sites by 4990 endoscopists. 89% of procedures were performed in NHS sites. 17% took place each weekday, 10% on Saturdays and 6% on Sundays. Training procedures accounted for 6% of total activity, over 99% of which took place in NHS sites. Median patient age was younger in the independent sector (IS) (51 vs 60 years, p<0.001). 74% of endoscopists were male. Gastroenterologists and surgeons each comprised one-third of the endoscopist workforce; non-medical endoscopists (NMEs) comprised 12% yet undertook 23% of procedures. Approximately half of endoscopists performing OGD (52%) or colonoscopies (48%) did not meet minimum annual procedure numbers. Conclusion: This comprehensive analysis reveals endoscopy workload and workforce patterns for the first time across both the NHS and the IS in all four UK nations. Half of all endoscopists perform fewer than the recommended minimum annual procedure numbers: a national strategy to address this, along with expansion of the NME workforce, would increase endoscopy capacity, which could be used to exploit latent weekend capacity.